Attentional mechanisms in light training tasks - Andria Shimi; Andria Shimi; Theofanis Kyriacou; Marios N. Avraamides; Marios N. Avraamides (Frontiers in Sports and Active Living)
IntroductionIn this study, we investigated the involvement of different aspects of attention in a light training task requiring fast physical responses to targets.MethodsFifty adult participants carried out drills in SpeedPad, a Virtual Reality (VR) adaptation of the Batak Pro and the Fitlight Trainer systems commonly used by athletes of various sports. Participants also carried out three established cognitive tasks on a desktop computer: the Posner cueing task, a visual conjunction search task, and a Motion Object Tracking (MOT) task.ResultsResults revealed significant correlations among performance on all four tasks, aligning with theoretical expectations. Regression analyses conducted for four array sizes in SpeedPad with 9, 15, 19, and 24 possible target locations, showed that the speed of attentional orienting to a target, measured with the Posner cueing task, was a significant predictor of SpeedPad performance across all array sizes. Accuracy in the MOT, which required splitting attention across multiple target locations and tracking moving targets, significantly predicted SpeedPad performance for array sizes 15, 19, and 24. However, the speed of visual search did not account for additional variance in SpeedPad performance beyond that explained by the other variables.DiscussionOverall, our results indicate that light training tasks like the SpeedPad rely on the efficient deployment of cognitive processes such as the spatial orienting of attention and the ability to split attention across multiple locations in the environment. These findings highlight the importance of cognitive skills for reacting fast to objects, suggesting that VR light training tasks could serve as valuable tools for exercising both cognitive and physiological processes in athletes across various sports.